1992
DOI: 10.1046/j.1537-2995.1992.32292180150.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hemolytic anemia associated with anti‐Sc1

Abstract: A case of autoimmune hemolytic anemia (AIHA) in a young child is described. The hemolysis was resistant to steroid therapy but responded to splenectomy and intravenous immunoglobulin. The autoantibody was shown to be anti-Sc1 by both serologic and immunoblotting techniques. This seems to be the first report of an autoanti-Sc1 detected by immunoblotting and the first example of AIHA in a child caused by autoanti-Sc1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The remaining patients with warm antibody AIHA have IgG autoantibodies that react with Rh-null RBCs [ 29 , 30 , 31 , 32 ]. Autoantibody specificity for these so-called non-Rh-related blood group antigens has been identified, including Wr b [ 29 ], En a [ 34 ], LW [ 35 ], U [ 36 ], Ge [ 23 , 37 ], Sc1 [ 38 ], and K [ 39 ].…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…The remaining patients with warm antibody AIHA have IgG autoantibodies that react with Rh-null RBCs [ 29 , 30 , 31 , 32 ]. Autoantibody specificity for these so-called non-Rh-related blood group antigens has been identified, including Wr b [ 29 ], En a [ 34 ], LW [ 35 ], U [ 36 ], Ge [ 23 , 37 ], Sc1 [ 38 ], and K [ 39 ].…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…McDowell et al 25 described two cases of autoimmune hemolytic anemia (AIHA) associated with auto anti-Sc1 due to transient suppression of Sc1. Similarly, Owen et al 26 described a case of severe, acute AIHA in infancy found in a West Indian girl that was associated with auto anti-Sc1. The hemolysis was resistant to steroid therapy, but was resolved following splenectomy and two courses of high-dose IVIG given perioperatively.…”
Section: Suppression Of Sc Antigens and The Production Of Sc Autoantibodiesmentioning
confidence: 87%
“…Introduction Scianna blood group system is carried on erythrocyte membrane-associated protein (ERMAP) (Wagner et al, 2003). Auto anti-Sc1 (Tregellas et al, 1979;Steane et al, 1982;McDowell et al, 1986;Owen et al, 1992) and anti-Sc3 (Peloquin et al, 1989) have been described, but is extremely rare. Case history/investigation A 61-year-old Caucasian female with Evan's syndrome and Ca breast with Hb 5Á5 g dL À1 was referred for investigation.…”
Section: P3mentioning
confidence: 99%